The Impact of Additional Ginkgo Biloba Extract on Cognitive Function in Acute Ischemic Stroke: A Systematic Review and Meta Analysis - Mohammad Sandhia Mahardhika Putra; Mutiyas Nadia Ulfa; Krisninda Anggonowati (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Stroke is the primary cause of mortality and disability among patients worldwide, and can cause cognitive impairment among these patients. Ginkgo Biloba Extract is an organic compound made from G. Biloba. The active ingredients in Ginkgo biloba extract have demonstrated some clinical benefits for cognitive impairment. Objective: We aim to investigate whether the addition of Ginkgo Biloba Extract to patients with acute ischemic stroke improves their cognitive function after follow-up. Methods: A literature search was conducted on PubMed, Google Scholar, and the Cochrane Database, without publication date limits, to identify studies investigating the effect of Ginkgo Biloba Extract on the cognitive function of patients with Acute Ischemic Stroke. The study's primary outcome is a change in cognitive status compared with the baseline, which was assessed with the Montreal Cognitive Assessment (MoCA) after follow-up. Results: Four randomized controlled trials with 3824 patients were identified. Based on the analysis, the addition of Ginkgo Biloba Extract had a significant impact on improving the MoCA score of acute ischemic stroke patients (MD = 0.47 [0.45-0.49], I2 = 76%, p < 0.00001). Conclusion: Additional Ginkgo biloba extract may improve cognitive function in patients with acute ischemic stroke.